Review Jembatan Sutami di Bandar Lampung - Nosya, Akhmad Dendi; Alami, Fikri; Sebayang, Surya (Universitas Lampung, 2018)
Many structural systems are available to build a bridge. One of them is prestressed concrete bridge. The purpose of this research is to review the design of prestressed concrete bridge using SAP 2000 ver. 14 software.This research use elastic method on prestressed concrete, and ultimate method on the design of the other structures on the bridge. Whereas finite element analysis (FEA) with SAP 2000 ver.14 is used on traffic load analysis . From the analysis results, the longitudinal girder requires bending reinforcement of 12 D13, skin reinforcement of 6 ∅13, and 18 strand with dia. of 0.5